Characterization Of Bamboo Gigantochloa Scortechinii at different ages. - Hamid, Norul Hisham; S., Othman; H., Rokiah; M., Abd. Latif; S., Ani; M., Mohd. Tamizi (Forest Research Institute Malaysia, 2006)
The anatomical, physical and chemical properties of Gigantochloa scortechinii from different ages of 0.5, 1.5, 3.5, 5.5 and 6.5 years were investigated. The bamboo culm from the sixth internode above ground was studied. This study suggests that G. scortechinii is in its growing, development and maturation phases at ages 0.5, 1.5 and 3.5 years respectively. The higher content of inorganic nutrients in bamboo showed its potential as chewing sticks. Bamboo from 3.5 years of age was suitable for any utilization purpose.